Раскопки некрополей Китея и Илурата в 2009 г. - Хршановский, В.А. (Археологічні дослідження в Україні, 2010)
Results of the research of two necropolei, in Ilurat and Cytae, are presented here. At the necropolis in Cytae, crypt 344 cut in a thin layer of limestone and subsoil clay was studied. It included a rectangular funeral chamber of 30 m2 and a short dromos leading from the east to the chamber. Finds from the crypt belonged to two chronological periods: from the 4th to the 3rd c. BC and from the 3rd to the 4th c. AD. The works at the necropolis in Ilurat were restricted to the research of the robbers’ trenches which appeared between the 2008 and 2009 seasons. In one of them room 228 probably of a ritual function was discovered. Based on the preliminary data it is dated by the 3rd and the 4th centuries.